Postdramatic tragedies - Cole, Emma ca. 20./21. Jh (Oxford University Press, 2020)
Ancient tragedy has played a well-documented role in contemporary theatre since the mid-twentieth century. In addition to the often-commented-upon watershed productions, however, is a significant but overlooked history involving classical tragedy in experimental and avant-garde theatre. Postdramatic Tragedies focuses upon such experimental reinventions and analyses receptions of Greek and Roman tragedy that come under the banner of 'postdramatic theatre', astyle of performance in which the traditional components of drama, such as character and narrative, are subordinate to the immediate, affective power of more abstract elements, such as image and sound. The chapters are arranged into three parts, each of which explores classical reception within a specificstrand of postdramatic theatre: text-based theatre, devised theatre, and theatre that transcends the usual boundaries of time and space, such as durational and immersive theatre. Each offers a semiotic and phenomenological analysis of a particular case study, covering both widely known and less studied productions from 1995 to 2015. Together they reveal that postdramatic theatre is related to the classics at its conceptual core, and that the study of postdramatic tragedies reveals a great dealabout both the evolution of theatre in recent decades, and the status of ancient drama in modernity
Keywords: Geschichte 1995-2015; Experimentelles Theater; Rezeption; Latein; Griechisch; Englisch; Tragödie